2021
DOI: 10.24852/pa2021.1.35.216.231
|View full text |Cite
|
Sign up to set email alerts
|

A Zooarchaeological and Molecular Assessment of Ancient Chicken Remains from Russia

Abstract: We here conduct ancient DNA analyses on 58 chicken bones from 15 archaeological sites (from the 9th to the 18th century AD) across the Volga region, the Leningrad region, the Pskov region, and the north of the Krasnoyarsk region to investigate genetic diversity of past chicken populations within this geographical area. We find all samples belong to sub-haplogroup E1, ubiquitous throughout the world and dominant in Europe, Africa and the Americas. This supports an introduction of chickens from the west, rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Chickens have been identified in other areas of the Roman Empire, including Italy 92 northern France 93 , Switzerland 94 , and northern Africa 95 , and even far northern Europe 96 . A recent synthesis of the zooarchaeological literature for Russia has illustrated that the chicken spread into western Russia and the river valleys of the steppe by 1,000 years ago and aDNA data suggested that it spread into the region from Europe rather than West Asia 97 . Despite the lack of data, we suggest that chicken likely simultaneously dispersed along a: 1) southern sea route; and 2) southern Himalayan and trans-Iranian/southern Central Asian route on its westward journey 17 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Chickens have been identified in other areas of the Roman Empire, including Italy 92 northern France 93 , Switzerland 94 , and northern Africa 95 , and even far northern Europe 96 . A recent synthesis of the zooarchaeological literature for Russia has illustrated that the chicken spread into western Russia and the river valleys of the steppe by 1,000 years ago and aDNA data suggested that it spread into the region from Europe rather than West Asia 97 . Despite the lack of data, we suggest that chicken likely simultaneously dispersed along a: 1) southern sea route; and 2) southern Himalayan and trans-Iranian/southern Central Asian route on its westward journey 17 , 43 .…”
Section: Discussionmentioning
confidence: 99%